2020
DOI: 10.5056/jnm20079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Psychobiotic Supplement on Serum Brain-derived Neurotrophic Factor Levels in Depressive Patients: A Post Hoc Analysis of a Randomized Clinical Trial

Abstract: Background/Aims Psychobiotics are probiotics or prebiotics that, upon ingestion in adequate amounts, yield positive influence on mental health via microbiota-gut-brain axis regulation to modulate the circulating cytokines, chemokines, neurotransmitters, or neurotrophins levels. We have recently shown that a psychobiotic combination (Lactobacillus helveticus R0052 and Bifidobacterium longum R0175; CEREBIOME) significantly improved depression symptoms in patients with depression. Recent animal data suggest the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 46 publications
(78 reference statements)
1
75
0
1
Order By: Relevance
“…C-reactive protein (CRP) was significantly reduced in the probiotic arm (compared to placebo) in a study that applied probiotics as adjunctive therapy [ 28 ], but not in a study of medication-free participants [ 33 ]. Similarly, BDNF was found to be significantly increased following probiotic treatment only when this was applied as adjunctive [ 36 ], and not as stand-alone treatment [ 33 ]. Interestingly, an inverse correlation between increases in BDNF and depression severity were also reported in this study [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…C-reactive protein (CRP) was significantly reduced in the probiotic arm (compared to placebo) in a study that applied probiotics as adjunctive therapy [ 28 ], but not in a study of medication-free participants [ 33 ]. Similarly, BDNF was found to be significantly increased following probiotic treatment only when this was applied as adjunctive [ 36 ], and not as stand-alone treatment [ 33 ]. Interestingly, an inverse correlation between increases in BDNF and depression severity were also reported in this study [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, BDNF was found to be significantly increased following probiotic treatment only when this was applied as adjunctive [ 36 ], and not as stand-alone treatment [ 33 ]. Interestingly, an inverse correlation between increases in BDNF and depression severity were also reported in this study [ 36 ]. The tryptophane/kynurenine ratio was measured in two add-on studies, but only found to significantly differ in one, with a reduction in the probiotic arm [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were predominantly conducted in Iran (N = 5) [21][22][23][24][25] but also in Austria (N = 2) [26,27], Poland (N = 1) [28] and Italy (N = 1) [29]. One study was conducted in two clinical centers, in Australia and Netherlands (N = 1) [30].…”
Section: Study Patient and Treatment Characteristicsmentioning
confidence: 99%